Sensory innervation of the lumbar 5/6 intervertebral disk in mice - Chen, Lunhao; Lu, Xuan; Jin, Qianjun; Gao, Zhihua; Wang, Yue (Frontiers in Neurology, 2023)
Introduction: Over the years, most back pain related biological studies focused on the pathogenesis of disc degeneration. It is known that the nerve distributions at the outer layer of the annulus fibrosus (AF) may be an important contributor for the back pain symptoms. However, types and origins of sensory nerve terminals in the mouse lumbar discs have not been widely studied. Using disc microinjection and nerve retrograde tracing methods, the current study aims to characterize the nerve types and neuropathway of the lumbar 5/6 (L5/6) disc in mice. Methods: Using an anterior peritoneal approach, the L5/6 disc of adult C57BL/6 mice (males, 8-12 weeks) was exposed to perform disc microinjection. Fluorogold (FG) was injected into the L5/6 disc using the Hamilton syringe with a homemade glass needle that driven by a pressure microinjector. The lumbar spine and bilateral thoracic 13 (Th13) to L6 DRGs were harvested at 10 days after injection. The number of FG+ neurons among different levels were counted and analyzed. Different nerve markers, including anti-neurofilament 160/200 (NF160/200), anti-calcitoningene-related peptide (CGRP), anti-parvalbumin (PV), and anti-tyrosine hydroxylase (TH), were used to identify different types of nerve terminals in AF and their origins in DRG neurons. Results: There were at least 3 types of nerve terminals at the outer layer of L5/6 AF in mice, including NF160/200+ (indicating Aβ fibers), CGRP+ (Aδ and C fibers) and PV+ (proprioceptive fibers). No TH+ fibers (sympathetic nerve fibers and some C-low threshold mechanoreceptors) was noticed in either. Using retrograde tracing methods, we found that nerve terminals in L5/6 disc were multi-segmentally from Th13-L6 DRGs, with L1 and L5 predominately. Immunofluorescence analysis revealed that FG+ neurons in DRGs were co-localized with NF160/200, CGRP and PV, but not TH. Conclusions: Intervertebral discs were innervated by multiple types of nerve fibers in mice, including Aβ, Aδ, C and proprioceptive fibers. No sympathetic nerve fibers were found in AF. The nerve network of L5/6 disc in mice was multi-segmentally innervated by the Th13-L6 DRGs (mainly L1 and L5 DRGs). Our results may serve as the reference for preclinical studies of discogenic pain in mice.